2018
DOI: 10.1021/acs.organomet.8b00776
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Amidines by Palladium-Mediated CO2 Extrusion Followed by Insertion of Carbodiimides: Translating Mechanistic Studies to Develop a One-Pot Method

Abstract: A palladium-mediated one-pot synthesis of amidines from aromatic carboxylic acids and carbodiimides (RNCNR) is reported as an isoelectronic adaption of CO 2 ExIn (ExIn = Extrusion−Insertion) reactions developed for the synthesis of thioamides from carboxylic acids and isothiocyanates (RNCS). Multistage mass spectrometry (MS n ) experiments for model systems established "proof of concept", demonstrating decarboxylation of [(L)Pd(O 2 CAr)] + (L = 1,10-phenanthroline or py), to give [(L)PdAr] + , followed by reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 80 publications
(132 reference statements)
2
23
1
Order By: Relevance
“… a X = OH, Y = S, see ref ; X = OH, Y = NR, see ref ; X = NHR, Y = O, see ref ; X = OH, Y = O, this work. …”
Section: Introductionmentioning
confidence: 98%
“… a X = OH, Y = S, see ref ; X = OH, Y = NR, see ref ; X = NHR, Y = O, see ref ; X = OH, Y = O, this work. …”
Section: Introductionmentioning
confidence: 98%
“…Due to the high stability of CO2, the overall reaction shown in eq. 38 is exothermic for the preparation of amides , thioamides (Noor et al, 2017) and amidines (Yang et al, 2019). In our studies of ExIn reactions, we showed that gas-phase (Scheme 26A) and solutionphase (Scheme 26B) mechanistic work on ligated palladium complexes can guide the development of one-pot synthetic methods for the palladium mediated ExIn synthesis of amides, thioamides and amidines (Scheme 26C).…”
Section: Author Manuscriptmentioning
confidence: 95%
“…These reactions involve organometallic intermediates rather than radicals, which tend to be unreactive in the key C-C bond-forming step unless they are nucleophilic radicals (Weragoda et al, 2018). Due to the high stability of CO 2 , the overall reaction shown in Equation 38 is exothermic for the preparation of amides , thioamides (Noor et al, 2017), and amidines (Yang et al, 2019).…”
Section: Development Of the New Class Of Exin Reactions For The Synthesis Of Amides Thioamides And Amidinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we were interested in developing a gasphase synthesis of ligated group 10 cations in the formal oxidation state of +1. We chose the [(phen)M(O2CCH3)] + complexes as suitable precursors since: the 1,10-phenanthroline (phen) ligand has been widely used in condensed phase synthetic and catalytic studies [28]; our previous work has shown that these complexes are readily generated via ESI-MS and readily fragment via decarboxylation [29] to generate organometallic cations, [(phen)M(CH3)] + , which undergo a number of interesting reactions of relevance to catalysis [30][31][32][33][34][35]; CID of related cations suggest that bond homolysis should occur [36]. Here we examine the use of bond homolysis reactions of [(phen)M(CH3)] + to generate the cations [(phen)M] +• for subsequent ion-molecule reaction studies with background water, O2 and N2 and the reagents acetone and allyl iodide.…”
mentioning
confidence: 99%